Pengaruh jus alpukat dan jus jambu biji terhadap kadar kolesterol total pada pengguna depo-medroxyprogesterone acetate - Rayana Iswani; Ernita Ernita; Erlina Erlina; Cut Mutiah; Agus Hendra Al Rahmad (Poltekkes Kemenkes Aceh, 2026)
Background: Depo-medroxyprogesterone acetate (DMPA) contraceptives are a cause of hypercholesterolemia. Natural treatments using fruits, specifically avocado and red guava, can be administered as preventive and curative measures to address this issue.Objectives: To determine the effects of red guava juice and avocado juice on reducing cholesterol levels among DMPA contraceptive users at the Banda Sakti Health Center.Methods: This study used a quasi-experimental method with a pretest-posttest two-group design. The research subjects were selected using accidental sampling; they comprised 60 mothers using DMPA contraceptives who experienced hypercholesterolemia at the Banda Sakti Health Center. The study was conducted from June to August 2024. The research process involved three stages: pretest measurement of cholesterol levels, a 14-day intervention with 250 mL/day of avocado juice and red guava juice, and posttest cholesterol measurement. The instrument used was an observation sheet, and data analysis was performed using the paired t-testResults: The mean cholesterol level before the avocado juice intervention was 228.07, which decreased to 204.73 after the intervention, with a mean difference of 23.33. The p-value was 0.000, indicating that avocado juice significantly affected the reduction of cholesterol levels in DMPA acceptors. In the guava juice group, the mean level before intervention was 227.53, decreasing to 211.13 afterward, with a mean difference of 16.40. With a p-value of 0.000, it was concluded that red guava juice also significantly impacted the reduction of cholesterol levels among DMPA acceptors at the Banda Sakti Health Center.Conclusion: Health workers should provide information, education, and counseling regarding effective non-pharmacological therapies for managing cholesterol levels among women using contraceptives.